2012
DOI: 10.1136/thoraxjnl-2012-201781
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of tissue factor lead to alveolar haemorrhage, potentiating murine acute lung injury and oxidative stress

Abstract: Background Systemic blockade of Tissue Factor (TF) attenuates acute lung injury (ALI) in animal models of sepsis but the effects of global TF deficiency are unknown. Hypothesis We used mice with complete knockout of mouse TF and low levels (~1%) of human TF (LTF mice) to test the hypothesis that global TF deficiency attenuates lung inflammation in direct lung injury. Methods LTF mice were treated with 10 μg of lipopolysaccharide (LPS) or vehicle administered by direct intratracheal (IT) injection and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 29 publications
(31 reference statements)
0
71
0
Order By: Relevance
“…All samples were stored at 280 8 C until further study. For histologic analysis, lungs were perfused with saline and inflated with formalin, as previously reported (2).…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…All samples were stored at 280 8 C until further study. For histologic analysis, lungs were perfused with saline and inflated with formalin, as previously reported (2).…”
Section: Sample Collectionmentioning
confidence: 99%
“…For direct LPS-induced lung injury, mice were anesthetized with isoflurane and treated with 10 mg LPS in 100 ml (Escherichia coli, LPS; Sigma, St. Louis, MO) or 100 ml PBS (control; Mediatech, Manassas, VA) by intratracheal injection (2,25). Indirect lung injury was induced by continuous infusion of LPS (8 mg/h for 24 h) or equal volume PBS delivered by osmotic pump (Durect, Cupertino, CA) with a single intraperitoneal dose of LPS (3 mg/mouse) or PBS at the time of pump implantation (26).…”
Section: Models Of Alimentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ARDS have evidence of increased RBCs and hemoglobin in tissues on histological sections (35). Studies in mice also indicate that there is hemorrhage and free hemoglobin in the intraalveolar space following intratracheal injection of LPS (36). In studies of patients with sepsis, elevated free plasma studies, hHx-B did not inhibit neutrophil migration to the peritoneal cavity induced by thioglycolate ( Figure 6).…”
Section: Discussionmentioning
confidence: 92%
“…Decreased TF activity in tissue samples contributes to high thromboplastin levels and cellular damage. Low levels of TF lead to alveolar hemorrhage, potentiating murine acute lung injury and oxidative stress (Bastarache et al, 2012). Emekli-Alturfan et al (2007) indicated a decrease in lung TF activity in STZ-treated rat.…”
Section: Discussionmentioning
confidence: 99%